Regulation of Arabidopsis thaliana seed dormancy and germination by 12-oxo-phytodienoic acid - Dave, Anuja (Journal of experimental botany, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the Society for Experimental Biology.